Experimental study and numerical simulation of seismic behaviour of corroded reinforced concrete frames. (January 2022) - Nagender, T.; Parulekar, Y.M.; Selvam, P.; Chattopadhyay, J.
Abstract: One of the major durability issues of Reinforced Concrete (RC) structures is the steel reinforcement corrosion. Its effect needs to be evaluated on the lateral load capacity of the structures for understanding their seismic performance. In the present paper, the precise FE modelling and simulation of corroded RC frames subjected to lateral loads and its validation with full scale shake table tests on corroded RC frames is demonstrated. The rebar corrosion is induced in RC frames by accelerated impressed current technique and shake table tests are performed by simulating real time earthquakes with increasing excitation till failure of the frames is achieved. The tests showed that there was higher degradation of the frequency of the corroded structure with respect to pristine structure with increase in earthquake excitation levels. Numerical simulation of the tests is carried out using 2D micro-modelling, incorporating the effect of bond strength reduction, reduction in rebar diameter and decrease in mechanical properties of corroded steel in the model. Nonlinear static pushover analysis is performed to evaluate load displacement characteristics of the corroded and uncorroded frames and the results are compared with dynamic pushover obtained from shake table tests. It was observed that compared to un-corroded frame there is 13% reduction in the failure load due to earthquake excitation for the 7.5% corroded frame and numerical results for 10% corroded frame showed 22% reduction in the lateral load carrying capacity.